2020
DOI: 10.1523/jneurosci.0502-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Multiplexing by Individual VTA Dopamine Neurons

Abstract: Dopamine (DA) neurons of the VTA track cues and rewards to generate a reward prediction error signal during Pavlovian conditioning. Here we explored how these neurons respond to a self-paced, operant task in freely moving mice. The animal could trigger a reward-predicting cue by remaining in a specific location of an operant box for a brief time before moving to a spout for reward collection. VTA DA neurons were identified using DAT-Cre male mice that carried an optrode with minimal impact on the behavioral ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 95 publications
6
42
1
Order By: Relevance
“…As a control, we analyzed neuronal activity during velocity peak randomly selected during the sessions, similar to velocity peak occurring during the transition events (Figure S5F–G). While some individual cells (35%) responded positively by increased firing during velocity peak (Figure S5H–I), strengthening the hypothesis of multiplexed information encoded by VTA pDA activity (Kremer et al., 2020), no changes were observed at the population level (Figure S5J). This data suggests a differential encoding in VTA pDA neurons depending on the target stimulus being approached, that is, toward the combined social experience offered by the juvenile versus the isolated social odor of the impregnated object.…”
Section: Resultssupporting
confidence: 76%
“…As a control, we analyzed neuronal activity during velocity peak randomly selected during the sessions, similar to velocity peak occurring during the transition events (Figure S5F–G). While some individual cells (35%) responded positively by increased firing during velocity peak (Figure S5H–I), strengthening the hypothesis of multiplexed information encoded by VTA pDA activity (Kremer et al., 2020), no changes were observed at the population level (Figure S5J). This data suggests a differential encoding in VTA pDA neurons depending on the target stimulus being approached, that is, toward the combined social experience offered by the juvenile versus the isolated social odor of the impregnated object.…”
Section: Resultssupporting
confidence: 76%
“…Previous studies report on the firing behavior of wild type (WT) rodent dopamine neurons [ 12 , 46 , 48 , 52 , 55 , 75 , 76 , 84 , 108 , 110 , 124 ] and have shown WT dopamine neurons exhibit both pacemaker-like firing activity and burst firing with an average rate of 0.5–10 Hz [ 46 ]. Studies also demonstrate a broader range of spontaneous spike frequency of 0–20 Hz in dopamine neurons [ 66 ]. In this study, we found the majority of NAS-derived dopamine neurons exhibited a mixture of single spikes and small burst activity with an underlying “pacemaker-like” periodicity.…”
Section: Resultsmentioning
confidence: 99%
“…VTA dopamine neurons form clusters encoding cognitive, motor and sensory variables and different subpopulations can encode different subsets of these variables (Engelhard et al, 2019). This complexity extends further to the task-dependent multiplexing of activity enabling appropriate goal-directed responding (Kremer et al, 2020).…”
Section: Ta Comple Xitie Smentioning
confidence: 98%
“…There are compartment-specific changes in dopamine signalling during relapse to alcohol-seeking. VTA dopamine neurons form functional clusters encoding cognitive, motor and sensory variables (Engelhard et al, 2019) and show task-dependent multiplexing of this activity to underpin appropriate behaviour (Kremer et al, 2020). In turn, their long-range projections to the ventral striatum form channels linked to differences in behavioural and motivational function (Cohen et al, 2012;Heymann et al, 2019;de Jong et al, 2019;Lammel et al, 2008Lammel et al, , 2011Lammel et al, , 2012Saunders et al, 2018;Tian et al, 2016;Watabe-Uchida et al, 2012) that are accompanied by distinct profiles of dopamine release and binding across compartments of the ventral striatum (de Jong et al, 2019;Mohebi et al, 2019).…”
Section: Find Ing the Dopamine S I G Nature S Of Rel Aps Ementioning
confidence: 99%